Deep foundations on bored and auger piles : proceedings of the fifth International Symposium on Deep Foundations on Bored and Auger Piles (BAP V), Ghent, Belgium, 8-10 September, 2008 /: proceedings of the fifth International Symposium on Deep Foundations on Bored and Auger Piles (BAP V), Ghent, Belgium, 8-10 September, 2008. (©2009) - Unknown
No abstract available